A comparative study of the efficacy and functionality of 10 commercially available wrist-hand orthoses in healthy females during activities of daily living - Alejandra Aranceta-Garza; Alejandra Aranceta-Garza; Karyn Ross (Frontiers Media S.A., 2022)
ObjectiveOptimal wrist/hand function facilitates the performance of activities of daily living (ADL), which are associated with independent living and increased quality of life. Rheumatological, musculoskeletal, and neurological conditions or injuries can negatively impact hand/wrist function, with wrist-hand orthoses (WHOs) being prescribed to control motion and improve wrist alignment whilst enhancing hand/wrist functionality. The objective of this follow-up study was to quantify and assess the efficacy and functionality of 10 commercially available WHOs during five ADLs.DesignRandomised comparative functional study of the wrist/hand with and without WHOs.ParticipantsTen right-handed healthy female participants with no underlying condition or pain affecting the wrist/hand that could influence their ability to undertake ADLs.Main outcome measuresThe primary outcome was ascertaining the impact of each WHO during five ADLs. Movement was quantified in sagittal, coronal, and transverse planes with and without WHO use. The resting position, maximum mean flexion, extension, pronation, supination, and radial and ulnar deviation attained were quantified, with the time spent in wrist flexion, wrist flexion and ulnar deviation, wrist extension >15°, and radial deviation recorded. Finally, the time to complete each task was compared between conditions.ResultsAt rest, four WHOs maintained the desired sagittal plane wrist position, with only one preventing radial deviation with variation observed in the transverse plane. All WHOs reduced mean maximum flexion, with only 10 out of 50 tests (20%) showing a successful restriction of flexion (p < 0.05) and 14 out of 50 (28%) showing a reduction of the time spent in flexion (p < 0.05). In 42 out of 50 tests (84%), the wrist was extended >15° for a significant amount of time (p < 0.05), with the wrist in radial deviation in 98% for a significant amount of time (p < 0.001). The wrist was flexed and in ulnar deviation for a significant time for 6 out of 50 tests (12%, p < 0.05), whilst all WHOs impacted transverse movement, with 27% reducing it significantly, and all tasks took a longer time to complete, with 46% taking a significantly longer time (p < 0.05).ConclusionThe WHOs did not control movement sufficiently to successfully manage any condition requiring motion restriction associated with pain relief and were found to increase the time to complete the ADLs. Multifactorial design aspects influenced functionality, and there is a clear need for WHO redesign.